Atomic Spalling of a van der Waals Nanomembrane - Moon, Ji Yun; Bae, Sang Hoon; Lee, Jae Hyun (Accounts of Chemical Research, 2024)
Conspectus The vertical integration of van der Waals nanomembranes (vdW NMs), composed of two-dimensional (2D) layered materials and three-dimensional (3D) freestanding films with vdW surfaces, opens new avenues for exploring novel physical phenomena and offers a promising pathway for prototyping ultrathin, superior-performance electronic and optoelectronic applications with unique functionalities. Achieving the desired functionality through vdW integration necessitates the production of high-quality individual vdW NMs, which is a fundamental prerequisite. A profound understanding of the synthetic strategies for vdW NMs, along with their fundamental working principles, is crucial in guiding the experimental design toward 3D integrated heterostructures. The foremost synthetic challenges in fabricating high-quality vdW NMs are achieving exact control over thickness and ensuring surface planarity on the atomic scale. Despite the development of numerous chemical and mechanical approaches to tackle these issues, an all-encompassing solution has yet to be realized. To address these challenges, we have developed advanced spalling techniques, specifically known as atomic spalling or 2D material-based layer transfer, which emerge as a promising technology for achieving both atomically precise thickness-engineered and atomically smooth vdW NMs. These techniques involve engineering the interfacial fracture toughness and strain energy in the vdW system, allowing for precise control over the initiation and the propagation of cracks within the vdW material based on controlled spalling theory. In this Account, we summarize our recent advancements in the atomic precision spalling technique for the preparation of vdW NMs and their applications. We begin by introducing the fundamentals of advanced spalling techniques, which are based on spalling mode fracture in bilayer systems. Following this, we succinctly describe the preparation methods for source materials for vdW NMs, with a primary focus on chemical synthesis approaches. We then delve into the working principles underlying our recent contributions to advanced spalling techniques, providing insights into how this method attains unprecedented atomic-precision control compared to other fabrication methods with a particular emphasis on tuning the interface between the stressor and the vdW system. Subsequently, we highlight cutting-edge applications based on vdW heterostructures, which combine our spalled vdW NMs. Finally, we discuss the current challenges and future directions for advanced spalling techniques, underscoring their potential to be established as a robust methodology for the preparation of high-quality vdW NMs. Our advanced spalling strategy not only ensures the reliable production of vdW NMs with exceptional control over thickness and atomic-level flatness but also provides a robust theoretical framework essential for producing high-quality vdW NMs.